The Relationship between XRCC1 and XRCC3 Gene Polymorphisms and Lung Cancer Risk in Northeastern Chinese - Guo, Shujie (Public Library of Science, 2013)
BACKGROUND: The prevalence of lung cancer in China will be the world's highest if allowed to proceed uncurbed. To unravel its genetic underpinnings, we sought to investigate the association of three well-characterized nonsynonymous polymorphisms in XRCC1 (Arg194Trp and Arg399Gln) and XRCC3 (Thr241Met) genes with lung cancer risk in northeastern Chinese. METHODOLOGY/PRINCIPAL FINDINGS: This study was hospital-based in design, encompassing 684 patients with lung cancer and 604 cancer-free controls. Genotyping was performed using the PCR-LDR (ligase detection reactions) method. Data were analyzed by R language and multifactor dimensionality reduction (MDR) software. Single-locus analysis identified significance in genotype distributions of polymorphism Arg194Trp (P = 0.002) and Arg399Gln (P = 0.017), and in allele distributions of Thr241Met (P = 0.005). Carriers of 399Gln/Gln genotype conferred a 147% increased risk relative to the non-carriers (odds ratio (OR): 2.47; 95% confidence interval (95% CI): 1.48–4.13; P<0.001). For Thr241Met, significance persisted under allelic (OR = 1.63; 95% CI: 1.14–2.33; P = 0.005), additive (OR = 1.64; 95% CI: 1.16–2.32; P = 0.005) and dominant (OR = 1.67; 95% CI: 1.17–2.38; P = 0.004) models. However, common allele combinations were comparable in frequency between patients and controls. In interaction analysis, the overall best MDR model included Arg399Gln and Thr241Met polymorphisms, with a maximal testing accuracy of 63.18% and a maximal cross-validation consistency of 10 out of 10 (P = 0.0175). CONCLUSIONS: Our study significantly demonstrated an independent and synergistic contribution of XRCC1 Arg399Gln and XRCC3 Thr241Met polymorphisms to lung cancer susceptibility in northeastern Chinese.